Shari’ah corporate governance structure of Malaysian Islamic banking and finance: the traces of shura - Mohd. Zain, Nor Razinah; Zulkarnain, Izyan Farhana; Hassan, Rusni (International Association of Islamic Banks, 2015)
Shari’ah Governance Framework for Islamic Financial Institutions 2010 or SGFI was introduced as an effort to establish and enhance the corporate governance structure which is in line with the requirements of Shari’ah. Opposite from the conventional corporate governance, the Shari’ah corporate governance has distinguished features where the priority is to fulfil the Shari’ah-compliant characteristics. By referring into the application of Shari’ah governance structure as operated within Malaysian Islamic banking and finance institutions, uniquely, there are traces of Shura concept where it is significant in achieving the objectives of Shari’ah corporate governance. This article explores the essence of Shari’ah corporate governance structure of Islamic banking and finance, the traces of concept of Shura and the relevancy of Shura in achieving the Shari’ah corporate governance in Malaysia.